Penerapan Tata Tertib Sekolah Dalam Meningkatkan Kedisiplinan Siswa Di SMAN 2 Soppeng Kabupaten Soppeng - Nurfadillah Nurfadillah; Muh. Sudirmn; Nurharsyah Khaer Hanafi (Jurnal Tomalebbi, 2022)
Abstract, This study aims: 1) To find out the application of student discipline in an effort to improve student discipline at SMAN 2 Soppeng, 2) To find out the obstacles faced by the school in implementing student discipline at SMAN 2 Soppeng, 3) To find out the teacher's strategies PPKn in applying discipline to students at SMAN 2 Soppeng. This type of research is a type of descriptive research using a qualitative approach. The data obtained from the results of this study were processed using data analysis with triangulation techniques. putup posters of order throughout the class. In its supervision, the school cooperates with all educators and education personnel in the school, while in giving sanctions it is carried out by giving a warning. Student rules imposed by schools can also contribute to improving student discipline because the rules contain a set of rules that aim to regulate students and students are obliged to comply with student rules imposed by the school. 2) Obstacles in the application of student discipline at SMAN 2 Soppeng consist of a lack of student understanding of the rules that apply, lack of self-awareness of students in complying with the rules, differences in student character, influence from the outside environment, lack of maximum supervision of the rules and the existence of social interests in schools become obstacles in the effort to implement the order to the fullest. 3) The strategies of Pancasila and Citizenship Education teachers in applying the rules to students are quite diverse, namely through example, providing direction or communication and by adjusting the rules to the conditions of the times.Keywords: Application of rules, discipline, students.